Using biochar and urea to improve rice production on tropical acid soils - Haruna, Ahmed Osumanu; Maru, Ali (Universiti Putra Malaysia Press, 2017)
This book demonstrates how chicken litter biochar can be uses as an organic amendment to condition acid soils to unlock phosphorus and potassium such that only mnimum amount of nitrogen fertilizers such as urea is used in rice cultivation. It also discusses how this approach can be used to increase nutrient use efficiency and rice grain yield. The book also highlights how soil nutrients conductivity and permittivity are related rice grain yield. This book will be a significant interest to those in the agricultural and environmental sciences, students, research scientist, farmers and others.